The Merdeka Curriculum Teaching Module at Raudhatul Athfal - Sri Marwiyati; Budi Setiyarini; Ni’matul Khayati; Revalina Maulida Nurul Hidayah; Shafira Rahma Aulia (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
The development of teaching modules in the Merdeka Curriculum is a strategic aspect of instructional planning, requiring teachers to design learning systematically, reflectively, and student-centered. However, challenges remain in comprehensively developing the components of the teaching modules. This study aims to analyze the level of alignment of teaching modules developed by Raudhatul Athfal (Raudhatul Athfal) teachers with the components of the Independent Curriculum for Early Childhood Education and to explore the challenges encountered in the development process. This study used a qualitative approach with a case study design. The subjects were Raudhatul Athfal (Raudhatul Athfal) teachers implementing the Independent Curriculum in early childhood groups, selected through purposive sampling. Data were collected through in-depth interviews, observations, and document analysis of the open module. Data analysis was conducted using descriptive qualitative methods, including data reduction, data presentation, and drawing conclusions to interpret the alignment of the open module components. The research results show that most components of the teaching modules have been structured according to the Independent Curriculum. However, several core sections, such as prompt questions and assessment instruments, as well as appendices such as enrichment, remedial materials, reading materials, and bibliographies, still need strengthening. These findings indicate the need for ongoing mentoring and training to improve teacher competency in designing more comprehensive and contextual teaching modules. The implications of this research emphasize the importance of professional support for teachers so that the implementation of the Independent Curriculum in early childhood education can run more optimally and impact the quality of learning.